Service life assessment of chloride affected bridge located in coastal region of India considering variation in the inherent structural parameters. (February 2020) - Borah, Mukunda Madhab; Dey, Abhijeet; Sil, Arjun
Abstract: Deterioration of RC bridges due to chloride induced corrosion is a grave concern worldwide. It occurs essentially, when the reinforcement embedded in concrete is exposed to marine or aggressive environments. Over the past few decades, many studies aimed at determining the parameters influencing the service life of structures affected by reinforcement corrosion. The aim of the present work is to put forward a reliable and simple service life model for predicting the useful life or period of RC bridges affected by chloride ingress and to validate the output of the model with the deterioration of an existing RC bridge structure. The application of the service life model has been done in an Indian bridge in the context of coastal environment. Parametric studies have been conducted in the model for examining the effect of various parameters such as water-cement ratio, reinforcement diameter, cover thickness, type of binder and corrosion rate on the variation of service life of the RC bridge structure. The results of the parametric study explained in a detailed manner so as to get an actual insight of the structural degradation mechanism for structures exposed to chemically aggressive environments.